2003
DOI: 10.1080/02786820300908
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Soot Nanoparticles in a Laminar Premixed Ethylene Flame by Scanning Mobility Particle Sizer

Abstract: Mobility size distributions of soot particles produced from a fuel-rich, laminar premixed ethylene flat flame were obtained by in situ probe sampling and online analysis using a nano scanning mobility particle sizer. The emphasis of the work was the development of an in situ sampling technique to follow the evolution of nanoparticles formed in flames. Particle size distribution functions were obtained along the centerline of the flame in a spatially resolved manner. Considerable efforts were made to eliminate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
126
2
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(136 citation statements)
references
References 16 publications
6
126
2
2
Order By: Relevance
“…The more recent studies of turbulent flames by Koylu and colleagues (Hu et al 2003(Hu et al , 2004Yang et al 2005) show the coexistence of the singlet spheroids and the carbonaceous aggregates and suggest that distributed particle nucleation occurs in these fuel-rich flames even in the presence of the larger soot aggregates. In this event, the particle size distribution (PSD) is clearly bimodal as has been found by the direct observations of laminar premixed flames (Zhao et al 2003;Öktem et al 2005).…”
Section: Precursor Nanoparticlesmentioning
confidence: 70%
See 1 more Smart Citation
“…The more recent studies of turbulent flames by Koylu and colleagues (Hu et al 2003(Hu et al , 2004Yang et al 2005) show the coexistence of the singlet spheroids and the carbonaceous aggregates and suggest that distributed particle nucleation occurs in these fuel-rich flames even in the presence of the larger soot aggregates. In this event, the particle size distribution (PSD) is clearly bimodal as has been found by the direct observations of laminar premixed flames (Zhao et al 2003;Öktem et al 2005).…”
Section: Precursor Nanoparticlesmentioning
confidence: 70%
“…However, micrographs from turbulent diffusion flames (Hu et al 2003(Hu et al , 2004Yang et al 2005) clearly show precursor nanoparticles in coexistence with mature aggregates. These images represent concrete evidence of a bimodal PSD that has been observed (Zhao et al 2003) in the premixed laminar flame using a scanning mobility particle sizer.…”
Section: Transformation Of Precursor Particles To Aggregatesmentioning
confidence: 99%
“…2) over a range of flame temperature and C/O ratios, using previously established experimental methods and procedures [44,49,50]. A schematic of the experimental arrangement for performing particle sampling and analysis by either SMPS or thermal desorption mass spectrometry is shown in Fig.…”
Section: Flat Flame Measurementsmentioning
confidence: 99%
“…Nevertheless, the determination of primary particle size distribution by using these techniques implies to record many images and the postprocessing is essentially controlled and consequently long and fastidious. For various soot origins and statistics levels, some authors found that size distributions of D p follows a normal distribution (Equation (1a)) (K€ oyl€ u and Faeth 1992;Wentzel et al 2003;Lapuerta et al 2007;Ouf et al 2008) and others found lognormal distributions (Equation (1b)) (Maricq et al 2003;Zhao et al 2003b;Mitchell et al 2006;Zhao et al 2007).…”
Section: Introductionmentioning
confidence: 99%